The Impact of Child Labour on Human Capital Formation in Nepal - Karna, Poonam Kumari Labh (EDUMALSYS Journal of Research in Education Management, 2025)
Nepal faces a persistent challenge with child labor, which has significant negative effects on the development of human capital. This study aims to explore the link between child labor and human capital development, specifically focusing on education, health, and skill development. The research investigates the socio-economic factors that contribute to child labor and its long-term impacts on the nation's workforce and economic growth. Using a mixed-methods approach, the study combines both quantitative data and qualitative insights to provide a thorough analysis. The findings emphasize the critical need for targeted interventions to break the cycle of poverty and child labor, ensuring the sustainable growth of human capital in Nepal.